2003
DOI: 10.1088/0954-3899/29/9/307
|View full text |Cite
|
Sign up to set email alerts
|

Study of pure annihilation type decaysB D sK

Abstract: In this work, we calculate the rare decays B 0 → D * − s K + and B + → D * + s K 0 in perturbative QCD approach with Sudakov resummation. We give the branching ratio of 10 −5 for B 0 → D * − s K + , which will be tested soon in B factories. The decay B + → D * + s K 0 has a very small branching ratio at O(10 −8 ), due to the suppression from CKM matrix elements |V * ub V cd |. It may be sensitive to new physics contributions. *

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…We also note that for the considered B c → D ðÃÞ S decays, the annihilation-type diagrams will provide sizable contributions to the amplitudes and even dominate the amplitudes due to the enhancement from the large CKM matrix elements V cb and V csðdÞ . It is worth mentioning that the PQCD approach is an effective approach for calculating the nonfactorizable and annihilation diagrams, which can be confirmed by the precise predictions for the B → J=ψD [22] and [23]. So, for these considered decay channels, the predictions in the PQCD approach are reliable.…”
Section: Introductionsupporting
confidence: 52%
“…We also note that for the considered B c → D ðÃÞ S decays, the annihilation-type diagrams will provide sizable contributions to the amplitudes and even dominate the amplitudes due to the enhancement from the large CKM matrix elements V cb and V csðdÞ . It is worth mentioning that the PQCD approach is an effective approach for calculating the nonfactorizable and annihilation diagrams, which can be confirmed by the precise predictions for the B → J=ψD [22] and [23]. So, for these considered decay channels, the predictions in the PQCD approach are reliable.…”
Section: Introductionsupporting
confidence: 52%
“…[13,14] for the recent developments and applications of the PQCD approach), to calculate the branching ratios, strong phases, and CP asymmetries. The perturbative QCD approach is formulated on the basis of k T factorization, and has been applied to B meson decays into charmed meson in a number of references and a global agreement of the results with the available data is found [15][16][17][18][19][20][21][22]. One of the most successful predictions is r K ¼ 0:092 þ0:012þ0:003 À0:003À0:003 [21], in good agreement with the data [7].…”
Section: Introductionmentioning
confidence: 62%
“…It is worth mentioning that in this framework, the so-called annihilation diagrams are also perturbatively calculable without introducing additional parameters [21,22]. The PQCD approach has been successfully used to study a number of pure annihilation type decays, and these predictions were confirmed subsequently in experiments [8,[22][23][24][25]. Thus, in our view, this method is reliable in dealing with the pure annihilation-type and annihilation-dominated decays as well.…”
Section: Introductionmentioning
confidence: 92%
“…This form factor effectively suppresses the end-point contribution of the distribution amplitude of the mesons in the small transverse momentum region, making the calculation in the PQCD approach reliable. It is worth mentioning that in this framework, the so-called annihilation diagrams are also perturbatively calculable without introducing additional parameters [21,22]. The PQCD approach has been successfully used to study a number of pure annihilation type decays, and these predictions were confirmed subsequently in experiments [8,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%